Oxidative Stress Promotes Instability of Regulatory T Cells in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis - Shimojima, Yasuhiro; Kishida, Dai; Ichikawa, Takanori; Takamatsu, Ryota; Nomura, Shun; Sekijima, Yoshiki (Frontiers in Immunology, 2021)
We investigated the characteristics of regulatory T cells (Tregs), focusing on the relationship between their stability and reactive oxygen species (ROS), in antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Intracellular expressions of effector cytokines, forkhead box protein 3 (FoxP3), ROS, phosphorylated mammalian target of rapamycin (mTOR), and sirtuin 1 (SIRT1) in Tregs from peripheral blood mononuclear cells (PBMCs) of patients with AAV and healthy controls (HC) were analyzed. The alterations in and functional ability of Tregs were compared before and after resveratrol (RVL) treatment of PBMCs in patients with AAV. Significantly higher expressions of interferon (IFN)-γ, interleukin (IL)-17, IL-4, ROS, and phosphorylated mTOR (pho-mTOR) and lower expression of SIRT1 in CD4+CD25+FoxP3+ cells were found in patients with AAV than in the HC. FoxP3 expression in CD4+CD25+ cells and suppressive function of Tregs were significantly lower in patients with AAV than in the HC. Tregs after RVL treatment demonstrated significant decreases in IFN-γ, ROS, and pho-mTOR levels and increases in FoxP3, SIRT1 levels, and functional activity. Conversely, the direct activation of SIRT1 by SRT1720 resulted in decreased FoxP3 expression, with no reduction in ROS levels. The pho-mTOR levels were significantly higher in Tregs after activation by SRT1720 than in those after RVL treatment. This study suggested that imbalanced changes in Tregs could be attributed to mTOR activation, in which ROS overproduction was predominantly implicated. Therefore, ROS is a key mediator for promoting Tregs instability in AAV.